A review of the Tourism Industry (Tour Operating Business and Travel Agency Business) Regulations 1992 & Tourism Industry (Tour Operating Business and Travel Agency Business) (Amendment) Regulations 2000. / Nuraisyah Chua Abdullah - Chua Abdullah, Nuraisyah (Research Management Institute (RMI), 2011)
The Standard Terms and Conditions for Outbound Tour Packages, Tourism Industry (Tour Operating Business and Travel Agency Business) Regulations 1992 (herein after referred to as Regulations 1992) is the first legislation which provides for the standardisation of terms of holiday contracts between the travel and tour operators and their respective holidaymakers. However, apart from the limitation of the application of the Regulations 1992, there are many provisions in the standard terms which pose problems to the travel agents and tour operators. The Tourism Industry (Tour Operating Business and Travel Agency Business) (Amendment) Regulations 2000 also does not remedy the problematic provisions in the Regulations 1992. In coming out with a proposal for the amendment of the Regulations 1992 feedbacks from MATTA members, is sought. The research proposed a more comprehensive coverage of the Regulations 1992 which include the standard terms and conditions for inbound tour packages, not exclusively binding only on the outbound tour package. The recommendations made at Chapter 5 very much takes into consideration the current development of the operation of other sub-sectors and the challenges which are faced by the tour and travel companies. Hence, the proposal seeks to provide better provisions for safeguarding the positions of both the travel companies as well as the tour members.